2018
DOI: 10.1093/intqhc/mzy188
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for intervention: stroke treatments, disability and mortality in urban Tanzania

Abstract: The 90-day mortality of stroke presenting at MNH is 50%, much higher than in higher income settings. Although severe stroke presentations are a major factor, efforts to improve the quality of care and prevent complications of stroke are urgently needed. Acute stroke interventions with low number needed to treat represent challenging long-term goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 44 publications
(32 reference statements)
1
17
2
Order By: Relevance
“…Stroke accounted for 5.5 million deaths and was the second leading cause of death globally in 2016 [1]. Stroke contributed to an overall mortality of 12% in Ethiopia between 2012 and 2014 [10] and 50% at 90 days following first ever stroke in Tanzania in 2017 [11].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke accounted for 5.5 million deaths and was the second leading cause of death globally in 2016 [1]. Stroke contributed to an overall mortality of 12% in Ethiopia between 2012 and 2014 [10] and 50% at 90 days following first ever stroke in Tanzania in 2017 [11].…”
Section: Introductionmentioning
confidence: 99%
“…For example in Uganda, 30-day mortality was found to be 43% compared to 27% in Gambia [6,9]. While 90-day mortality was estimated at 50% in Tanzania compared to 29.4% in Korea [10,11]. Furthermore, studies in Nigeria and South Africa, indicated that overall mortality at 1 month ranged between 30 and 35% [12,13].. Reports have shown that mortality rates increased with increasing age and were higher for hemorrhagic stroke (HS) than for ischaemic stroke (IS) and, is often associated with a higher risk of early death [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies in Nigeria and South Africa, indicated that overall mortality at 1 month ranged between 30 and 35% [12,13].. Reports have shown that mortality rates increased with increasing age and were higher for hemorrhagic stroke (HS) than for ischaemic stroke (IS) and, is often associated with a higher risk of early death [9,14]. Previous studies have linked the excess mortality in patients with HS to more severe strokes [11,15]. In Dublin, using the modified Ranking Scale (mRS), overall good outcome at 28 days was more common in IS (44.4%) compared with HS (26.8%) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemic strokes due to large vessel occlusion (LVO) account for the largest proportion of stroke‐related disability and death 1,2 . Endovascular thrombectomy (EVT) has revolutionized the acute care of these patients, 3–5 but over half are functionally disabled or dead at 90 days despite treatment 3 .…”
Section: Introductionmentioning
confidence: 99%